COMMUNICATIVE VALIDITY OF THE NEW CET-4 LISTENING COMPREHENSION TEST IN CHINA - Wang, Chao (Indonesian Journal of Applied Linguistics, 2014)
Abstract: Based on the major dimensions of a communicative language test that Bachman proposed, this paper aims to have an investigation on the validity of the new CET-4 listening subtest in China from a communicative point of view. Both qualitative and quantitative methods are involved in the study. Material analysis falls into qualitative study, including analysis of the CET-4 testing syllabus and eight new CET-4 listening comprehension tests. Students’ scores of two tests and the questionnaires are analyzed quantitatively. Through analysis, it is found that the new CET-4 listening subtest has a high validity and can measure test-takers’ listening ability in real communication. First, the new CET-4 listening subtest has the quality of reliability. Second, the seven listening skills tested in this subtest can measure the communicative language ability required in the testing syllabus. The intra-correlation analysis shows that each part of the new CET-4 listening subtest focuses on different language abilities related to listening. Third, the authenticity of the new CET-4 listening subtest reaches a satisfactory level. The materials chosen in the test cover various topics and genres. Speakers’ pronunciation, tone and speed are in accordance with the real situation. However, some shortcomings also exist in the test design and should be improved later. For example, its limited item types cannot represent the task types in real life, and the actual input is too ideal to be authentic. Keywords: Communicative language ability, communicative language testing, listening comprehension, test validity